Aktivasi Subang sebagai Habitat Ekosistem Angklung Ragam Laras: Studi Kasus pada Sanggar Toléater | Activation of Subang as an Ecosystem Habitat for Angklung Ragam Laras: A Case Study of Sanggar Toléater - Irawan, Endah; Ridwan, Indra; sentosa, Gempur; Sudrajat, Mustika Iman Zakaria; Karwati, Uus; Sutanto, Toni Setiawan (GHURNITA: Jurnal Seni Karawitan, 2024)
After the establishment of Angklung as a world cultural heritage by UNESCO, there are consequences for Indonesia to protect, develop, utilize, and foster the life of Angklung. One of the efforts to face these consequences is to activate the angklung ecosystem in Subang Regency as a development effort so that angklung as a world heritage can maintain its existence. This research uses an experimental approach by providing training to Sanggar Toleater through a process of socialization, data collection, and work training in an art governance workshop, which ends with an evaluation; it is hoped that with this approach, this research and experimentation can protect the life of angklung that lives sustainably.